2016
DOI: 10.3390/diagnostics6030028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Tumor Response to Treatment in Patients with Lung Cancer Using Dynamic Contrast-Enhanced CT

Abstract: The aim of this study was to provide an overview of the literature available on dynamic contrast-enhanced computed tomography (DCE-CT) as a tool to evaluate treatment response in patients with lung cancer. This systematic review was compiled according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Only original research articles concerning treatment response in patients with lung cancer assessed with DCE-CT were included. To assess the validity of each study we imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…To date, CTP based on a single-input model has been investigated for the evaluation of various treatments of lung cancer, including chemotherapy, targeted therapy, radiotherapy and interventional therapy. The majority of these studies confirmed CTP as a useful method and found that BF and permeability surface (PS) product decreased after treatment (33)(34)(35)(36)(37). Few studies have been carried out on thermal ablation, and the results have varied.…”
Section: Discussionmentioning
confidence: 99%
“…To date, CTP based on a single-input model has been investigated for the evaluation of various treatments of lung cancer, including chemotherapy, targeted therapy, radiotherapy and interventional therapy. The majority of these studies confirmed CTP as a useful method and found that BF and permeability surface (PS) product decreased after treatment (33)(34)(35)(36)(37). Few studies have been carried out on thermal ablation, and the results have varied.…”
Section: Discussionmentioning
confidence: 99%
“…For patients receiving chemotherapy or radiation, CT scan is an excellent method of monitoring tumour progression and response. 31…”
Section: Discussionmentioning
confidence: 99%